LIMESTONE BEDS DEVELOPMENT OF THE MIDDLE–LATE MIOCENE JATILUHUR FORMATION IN THE BOGOR TROUGH, WEST JAVA - -, Abdurrokhim; -, Hendarmawan (Fakultas Teknik Geologi Universitas Padjadjaran, 2015)
The sedimentary rock succession of the Jatiluhur Formation comprises of mixed siliciclastic and carbonate sedimentary rocks. Two intervals of limestone beds are observed along the Cipamingkis River, on the lower and upper part of succession. Limestone in the lower part is typified by coarse-grained slump-scar-fill deposits that deposited during middle Miocene. It is largely consisting of skeletal fragments that have been delivered from the shallow marine carbonate reef of the Upper Cibulakan Formation during relative sea level fall. The punctuated mixing of siliciclastic and carbonate detritus took place during the middle Miocene in the Bogor Trough. Limestone beds in the upper part are characterized by thick- to very thick bedded limestone intercalated with thin- to very thin laminated siltstone, claystone, and fine-grained sandstone, which are interpreted to have been deposited in the shelf margin environment during late Miocene. The limestone consists of various characteristic of packstone, grainstone, rudstone and boundstone. Carbonate reef of the Klapanunggal Formation is interpreted to be the source of thick-bedded limestone in the upper part. The facies mixing of siliciclastic and carbonate sediments occurred in the middle part of Jatiluhur Formation during the late Miocene.